Chronology of Coastal Alluvial Deposits in The Ria de Coruña (NW Spain) Linked to the Upper Pleistocene Sea Level Regression - Carlos Arce-Chamorro; Jorge Sanjurjo-Sánchez; Juan Ramón Vidal-Romaní (Applied Sciences, 2022)
The Ria de Coruña (NW Spain) is a wide estuary recently formed by the flooding of the Mero fluvial valley lowlands during the last postglacial transgression. During the last glacial episode, with the sea level located more than 100 m below the current one, the final section of the Mero river and lateral tributaries contributed numerous deposits that the postglacial rise in sea level has partially flooded. Until now, the presence of these alluvial deposits disconnected from the main network by the Holocene marine transgression had been misinterpreted, especially for lack of an absolute chronology that would place them in an adequate paleoclimatic context. For the first time, a deposition age was assessed in this work by optically stimulated luminescence (OSL) dating back from 128 ka to 51 ka.